2007
DOI: 10.1038/sj.ki.5002422
|View full text |Cite
|
Sign up to set email alerts
|

Iron sucrose causes greater proteinuria than ferric gluconate in non-dialysis chronic kidney disease

Abstract: Non-dextran intravenous (i.v.) iron preparations seem to differentially affect proteinuria in patients with chronic kidney disease. To study effects of ferric gluconate and iron sucrose on proteinuria, we conducted a crossover trial in 12 patients with stage 3-4 chronic kidney disease. These patients were randomized to receive the same dose of either drug 1 week apart. Urine samples were obtained immediately before and at frequent intervals after the drug. The urine total protein/creatinine ratio was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 11 publications
2
26
1
Order By: Relevance
“…On the other hand, ferric gluconate at two dosage levels (125 and 250 mg) administered to iron-deficient anemic patients with CKD found that although ferric gluconate caused oxidative stress, there was no evidence of acute renal injury (12). In our earlier crossover, randomized, single-dose exposure trial comparing ferric gluconate to iron sucrose, we demonstrated that the urine total protein-to-creatinine ratio was significantly greater after iron sucrose than ferric gluconate treatment with the effect noted within 15 minutes after infusion (13). Furthermore, when iron sucrose was given first, a significantly greater protein-to-creatinine ratio was seen subsequently with ferric gluconate than with the reverse order of treatment.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, ferric gluconate at two dosage levels (125 and 250 mg) administered to iron-deficient anemic patients with CKD found that although ferric gluconate caused oxidative stress, there was no evidence of acute renal injury (12). In our earlier crossover, randomized, single-dose exposure trial comparing ferric gluconate to iron sucrose, we demonstrated that the urine total protein-to-creatinine ratio was significantly greater after iron sucrose than ferric gluconate treatment with the effect noted within 15 minutes after infusion (13). Furthermore, when iron sucrose was given first, a significantly greater protein-to-creatinine ratio was seen subsequently with ferric gluconate than with the reverse order of treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Although iron sucrose was associated with worsening of proteinuria, ferric gluconate was not (11,12). In a single dose head-to-head comparison of iron sucrose and ferric gluconate, iron sucrose was found to elicit greater proteinuria (13). Because proteinuria is strongly linked to accelerated progression to ESRD and cardiovascular disease, concerns regarding IV iron have been raised in the long term (6).…”
Section: Introductionmentioning
confidence: 99%
“…Oral iron has more GI associated side effects including constipation, diarrhea, nausea and vomiting. [13][14][15][16][17] As a result of these studies the K/DOQI guidelines have recommended that either oral iron therapy or intravenous iron therapy can be given in CKD patients.…”
Section: Anemia In Chronic Kidney Diseasementioning
confidence: 99%
“…Both oral and IV iron similarly increased Hb in anemic CKD patients not receiving ESAs. 16 A new IV iron preparation, ferumoxytol has been approved in the United States. It appears to be safe and effective when given as a rapid infusion of up to 510 mg in patients with CKD and patients on dialysis.…”
Section: Anemia In Chronic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation